PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN LANSIA DALAM MEMANFAATKAN POSYANDU LANSIA - Yuliani; Agustina, Rismia; Rachmawati, Kurnia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
The elderly are vulnerable groups to diseases, primarily degenerative diseases. One of the efforts tomaintain health of the elderly is by increasing their participation in using elderly Posyandu.Participation in elderly posyandu can be increased by health education the elderly. The purpose ofthis study was to determine the effect of health education on elderly knowledge in utilizing the elderlyposyandu in Bi-ih village of Karang Intan Public Health Center region Banjar. The design was Preexperimental design:one group pretest-postest. The population in this study was all elderly aged 45-55 years, the sample was 35 elderly in the village of Bi-ih. The data was gathered usingquestionnaire. Data analysis was performed using the wilcoxon test and showed knowledge increasesignificantly elderly p = 0,000 (p<0,05). It indicates the influence of health education on elderlyknowledge in utilizing elderly Posyandu in Bi-ih village of Karang Intan Public Health CenterBanjar. It is expected to increase the implementation of health education so that people can haveenough knowledge about health.